Emergency department contribution to HCV elimination in the Iberian Peninsula - Maria Buti; Inês Vaz-Pinto; Vítor Magno Pereira; Marta Casado; Jordi Llaneras; Ana Barreira; Catarina Esteves; Mafalda Guimarães; Ana Gorgulho; Tomás Mourão; Elisa Xavier; Luís Jasmins; et al. (International Journal of Emergency Medicine, 2024)
Abstract Background Undiagnosed cases of hepatitis C virus (HCV) infection result in significant morbidity and mortality, further transmission, and increased public health costs. Testing in emergency departments (EDs) is an opportunity to expand HCV screening. The goal of this project was to increase the proportion of eligible patients screened for HCV in urban areas. Methods An opportunistic automated HCV screening program was implemented in the EDs of 4 public hospitals in Spain and Portugal at different periods between 2018 and 2023. HCV prevalence was prospectively evaluated, and single-step or reflex testing was used for confirmation in the same sample. Results More than 90% of the population eligible for testing were screened in the participating centers. We found HCV antibody seroprevalence rates ranging from 0.6 to 3.9%, with between 19 and 53% of viremic individuals. Conclusions Opportunistic HCV screening in EDs is feasible, does not disrupt ED activities, is highly effective in increasing diagnosis, and contributes to WHO’s HCV elimination goals.